Genetic diversity and variation in antimicrobial-resistance determinants of non-serotype 2 Streptococcus suis isolates from healthy pigs. Issue 11 (3rd November 2022) - Kittiwan, Nattinee; Calland, Jessica K.; Mourkas, Evangelos; Hitchings, Matthew D.; Murray, Susan; Tadee, Pakpoom; Tadee, Phacharaporn; Duangsonk, Kwanjit; Meric, Guillaume; Sheppard, Samuel K.; Patchanee, Prapas; Pascoe, Ben
Abstract : Streptococcus suis is a leading cause of bacterial meningitis in South-East Asia, with frequent zoonotic transfer to humans associated with close contact with pigs. A small number of invasive lineages are responsible for endemic infection in the swine industry, causing considerable global economic losses. A lack of surveillance and a rising trend in clinical treatment failure has raised concerns of growing antimicrobial resistance (AMR) among invasive S. suis . Gene flow between healthy and disease isolates is poorly understood and, in this study, we sample and sequence a collection of isolates predominantly from healthy pigs in Chiang Mai province, Northern Thailand. Pangenome characterization identified extensive genetic diversity and frequent AMR carriage in isolates from healthy pigs. Multiple AMR genes were identified, conferring resistance to aminoglycosides, lincosamides, tetracycline and macrolides. All isolates were non-susceptible to three or more different antimicrobial classes, and 75 % of non-serotype 2 isolates were non-susceptible to six or more classes (compared to 37.5 % of serotype 2 isolates). AMR genes were found on integrative and conjugative elements previously observed in other species, suggesting a mobile gene pool that can be accessed by invasive disease isolates. This article contains data hosted by Microreact .